PENERAPAN APLIKASI SISTEM INFORMASI ELETRONIK LAPORAN PENYELENGGARAAN PEMERINTAHAN DAERAH (SI-ETA) DI LINGKUNGAN PEMERINTAH KOTA GORONTALO - Suleman, Sinta; Pakaya, Roys (Universitas Muhammadiyah Gorontalo, 2024)
The Regional Government Implementation Reporting Application within the Gorontalo City Government is an information system designed to increase efficiency, transparency and accountability in the implementation of regional government duties and responsibilities. This application aims to simplify the reporting process for regional government administration, facilitate access to information for the public, and strengthen internal monitoring mechanisms. By utilizing information technology, this application provides a platform that allows government administrators in Gorontalo City to report their activities, projects and performance achievements in a structured manner. The collected data can be accessed by related parties, including the general public, through a user-friendly interface. This provides opportunities for active community participation in monitoring and evaluating local government performance. This application is also equipped with adequate security features to protect sensitive data and maintain information integrity. Additionally, strong authentication mechanisms are implemented to ensure that incoming reports come from legitimate sources. The sustainability and development of this application is guaranteed through ongoing maintenance and adjustment in accordance with the needs and changes in the local government environment. By implementing the Regional Government Administration Reporting Application, it is hoped that it can create a system that is responsive, transparent and responsible, so that it can have a positive impact on the quality of public services and development in Gorontalo City.